What changed when everything changed 9/11 and the making of national identity - Margulies, Joseph (Yale University Press, 2013)
"In this startling analysis of the direction of America's political conversation since the events of September 11, 2001, Joseph Margulies traces the evolution of American identity. He shows that for key elements of the post-9/11 landscape--especially support for counterterror policies like torture and hostility to Islam--American identity is not only darker than it was before September 11, but substantially more repressive than it was immediately after the attacks. Even more surprising, this appetite for repressive policies has developed while the terrorist threat has declined. As the counsel of record in 2004 for the first Supreme Court case regarding detentions at Guantanamo Bay, and later the counsel of record for the first and only Supreme Court cases involving overseas detention of U.S. citizens in the war on terror, Margulies has direct real-life experience with these changes in values. He shows that in the immediate aftermath of 9/11 there was a shared determination to preserve national identity. But since then the national narrative has unexpectedly veered off course, becoming far more repressive and alarmist as the threat has abated. Margulies argues persuasively that beneath our common language about shared ideals, American values are surprisingly fluid, and he warns, "National identity is not fixed, it is made."--Jacket